Responses of Plant Biomass in the Brazilian Savanna to Frequent Fires - Gomes, Letícia; Miranda, Heloisa Sinátora; Soares-Filho, Britaldo; Rodrigues, Lucas; Oliveira, Ubirajara; Bustamante, Mercedes M. C. (Frontiers in Forests and Global Change, 2020)
Fire has been a natural feature of the ecosystem for million years. Still, currently fire regimes have been increasingly altered by human activities and climate change, causing economic losses, air pollution, and environmental damage. In Brazil, savannas (locally known as the Cerrado) occupy almost 25% of the area of the country and contain 70% of the concentrated burned area. Fire frequency is related to the use of biannual fire in agricultural practices, aiming at cleaning cattle pastures, which act as ignition sources for the surrounding natural vegetation. Here, we present an ecological model to demonstrate how biennial fire affects plant biomass and carbon release from fine fuel in the Cerrado. The BEFIRE model (Behavior and Effect of Fire) is the first quantitative model to simulate the relationships between fire frequency, plant biomass, and fire-associated emissions based on the synthesis of knowledge about fire behavior and the effects on ecosystems compiled from experimental burnings in the Cerrado. Our model uses microclimate variables and vegetation structure (the amount of the aboveground biomass of trees, shrubs, herbs, and grasses) as inputs, and generates outputs related to the fire behavior (fire spread rate, fire intensity, and heat released) and the fire effects on the dynamic of plant biomass and post-fire carbon emissions. The BEFIRE model predicts that biennial fires allow for the recovery of the biomass of herbs and grasses, due to its fast growth. However, this fire interval does not allow for the recovery of the biomass of shrubs and trees. These growth limitations alter the co-existence of trees/shrubs and herbs/grasses and prevent the uptake of the total amount of emitted carbon from the combustion of fine fuel. Based on the model results, we proposed some recommendations for fire management in this threatened biome.